Analysis of oil displacement and residue distribution in microheterogeneity reservoir. Issue 2 (1st February 2022) - Dong, Lifei; Wang, Miao; Wang, Wei; Ding, Mingchen; Lin, Hun
Abstract: In order to discuss the influence of microheterogeneity on oil displacement and residue distribution, the parallel capillary model is established, and the forming and finally distribution of remaining oil after water flooding is analyzed. To verify the theoretical model and to discuss the remaining oil further, two experimental models with the property of microheterogeneity are designed, which are the visual sand-packed model visual model and the man-made sandstone core slab model, according to the similarity principle. And the video observation method is used during the oil displacement experiments in visual sand-packed model visual model, while the resistivity test is taken in the sandstone core slab model experiments. The results show that the microheterogeneity can cause the different oil seepage ability between low permeability area and high permeability area relatively. It also makes the instability oil–water front and the heavy fingering during oil displacement in microheterogeneity reservoir. The remaining oil is formed and mostly located in the low permeability area and the hydrodynamic retention places among them., which is consistent with the theoretical model. Long-term water flooding can only reduce the saturation of remaining oil nearby the water injection inlet. So the main direction to enhance oil recovery in microheterogeneity reservoir is to improve the microsweep efficiency. Graphical abstract: UF0001 In this paper, the parallel capillary model is established and two experimental models are designed to simulate the characteristic of micro heterogeneity in reservoirs. The seepage characteristic is displayed during water flooding from the two experimental models. Also, the front of water saturation and the distribution of remaining oil during water flooding are described with the methods of video observation and resistivity test. The results show that the micro heterogeneity can easily cause the instability oil-water front and the heavy fingering during oil displacement. Long-term water flooding causes the heavy water channeling and makes low micro sweep efficiency as the micro heterogeneity. The remaining oil is mostly located in the low permeability areas and the hydrodynamic retention places among them. The best way to enhance oil recovery for micro heterogeneity reservoirs is to improve the micro sweep efficiency.